Dynamic Function and Composition Shift in Circulating Innate Immune Cells in Hibernating Garden Dormice - Huber, Nikolaus; Vetter, Sebastian; Stalder, Gabrielle; Gerritsmann, Hanno; Giroud, Sylvain (Frontiers in Physiology, 2021)
Hibernation is characterized by successive torpor bouts during which metabolic rate is down-regulated to 2–4% of euthermic levels along with core body temperatures (Tb) ranging between 0 and 10°C. One characteristic of the torpid state, which is periodically interrupted by a few hours of euthermic phases or arousals during hibernation, resides in an overall impairment of the immune system. The most striking change during torpor is the reduction of circulating white blood cells up to 90%, while their numbers rise to near summer euthermic level upon rewarming. However, potential changes in responsiveness and function of neutrophil granulocytes, accounting for the primary cellular innate immune defense, are unknown. Here we present the first data on shifts in oxidative burst capacity, i.e., the ability to produce reactive oxygen species (ROS), of neutrophils during hibernation. Using a chemiluminescence assay, we measured real-time ROS production in whole blood of hibernating garden dormice (Eliomys quercinus) in early or late torpor, and upon arousals. Accounting for changes in neutrophil numbers along the torpor-arousal cycle, we found significant differences, between torpid and euthermic states, in the neutrophil oxidative burst capacity (NOC), with shallow cell responses during torpor and a highly significant increase by up to 30-fold during arousals. Further, we observed a significant reduction of NOC from aroused animals with euthermic Tb of 36.95 ± 0.37°C, when tested at 6°C, whereas no change occurred in NOC from torpid individuals reaching constant Tb of 4.67 ± 0.42°C, when measured at 35°C. This dynamic indicates that the reduction in NOC during torpor may be temperature-compensated. These results linked to the understanding of immune function during the torpor-arousal cycle might have clinical relevance in the context of therapeutic hypothermia and reperfusion injury.